Antioxidant and Antimalarial Properties of Nigella sativa - Sam, Jian Hung; Chan, Yen San; Angela, Siner (International Journal of Chemical Engineering and Applications., 2024)
Throughout the years, natural products have become a vital component contributing immensely to the healthcare industry. These natural products are highly valued for their diverse bioactive compounds which exhibit a wide range of medicinal properties and possess the potential for disease control or prevention. Nigella sativa, also known as black cumin, is originally native to Southern Europe, North Africa, and Southwest Asia. It is also cultivated in Malaysia and its seed serves as a culinary ingredient in the local cuisine. The seed of Nigella sativa has also been used by indigenous tribes around the world since long ago for traditional remedies. The objectives of this research are to evaluate the antioxidant activity and the antimalarial activity of the methanolic Nigella sativa extract. The DPPH assay yielded an antioxidant activity of 6.42% at 0.2 mg/ml. While, in the Mark III assay, the antimalarial activity exhibited dose-dependent results at concentrations of 1.56 µg/ml, 3.13 µg/ml, 6.25 µg/ml, 12.50 µg/ml, 25.00 µg/ml, 50.00 µg/ml and 100.00 µg/ml. In summary, the methanolic extract from Nigella sativa exhibits antioxidant potential which might also play a significant role in the management of malaria.